Psychology and hereditary angioedema: A systematic review - Savarese, Livia (Allergy Asthma Proc, 2021)
BACKGROUND: Hereditary angioedema (HAE) is caused by mutations in the C1 inhibitor (C1-INH) gene Serpin Family G Member 1(SERPING1), which results in either the decreased synthesis of normal C1-INH (C1-INH–HAE type I) or expression of unfunctional C1-INH (C1-INH–HAE type II). In recent studies, emotional stress was reported by patients as the most common trigger factor for C1-INH–HAE attacks. Moreover, patients reported considerable distress over the significant variability and uncertainty with which the disease manifests, in addition to the impact of physical symptoms on their overall quality of life. OBJECTIVE: We did a systematic review of the literature to shed light on the advancements made in the study of how stress and psychological processes impact C1-INH–HAE. METHODS: All of the articles on C1-INH–HAE were analyzed up to December 2019. Both medical data bases and psychological data bases were examined. The keywords (KWs) used for searching the medical and psychological data bases were the following: “hereditary angioedema,” “psychology,” “stress,” “anxiety,” and “depression.” RESULTS: Of a total of 2549 articles on C1-INH–HAE, 113 articles were retrieved from the literature search by using the related KWs. Twenty-one of these articles were retrieved, examined, and classified. CONCLUSION: Although the literature confirmed that stress may induce various physical diseases, it also warned against making simplistic statements about its incidence that did not take into account the complexity and multicausality of factors that contribute to C1-INH–HAE expression.